Risk factors associated with preterm birth after IVF/ICSI - Li, Jian; Shen, Jinhua; Zhang, Xiaoli; Peng, Yangqin; Zhang, Qin; Hu, Liang; Reichetzeder, Christoph; Zeng, Suimin; Li, Jing; Tian, Mei; Gong, Fei; Lin, Ge; et al. (Scientific reports, 2022)
In vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) is associated with an increased risk of preterm (33rd-37th gestational week) and early preterm birth (20th-32nd gestational week). The underlying general and procedure related risk factors are not well understood so far. 4328 infertile women undergoing IVF/ICSI were entered into this study. The study population was divided into three groups: (a) early preterm birth group (n = 66), (b) preterm birth group (n = 675) and (c) full-term birth group (n = 3653). Odds for preterm birth were calculated by stepwise multivariate logistic regression analysis. We identified seven independent risk factors for preterm birth and four independent risk factors for early preterm birth. Older (> 39) or younger (< 25) maternal age (OR: 1.504, 95% CI 1.108-2.042, P = 0.009; OR: 2.125, 95% CI 1.049-4.304, P = 0.036, respectively), multiple pregnancy (OR: 9.780, 95% CI 8.014-11.935, P < 0.001; OR: 8.588, 95% CI 4.866-15.157, P < 0.001, respectively), placenta previa (OR: 14.954, 95% CI 8.053-27.767, P < 0.001; OR: 16.479, 95% CI 4.381-61.976, P < 0.001, respectively), and embryo reduction (OR: 3.547, 95% CI 1.736-7.249, P = 0.001; OR: 7.145, 95% CI 1.990-25.663, P = 0.003, respectively) were associated with preterm birth and early preterm birth, whereas gestational hypertension (OR: 2.494, 95% CI 1.770-3.514, P < 0.001), elevated triglycerides (OR: 1.120, 95% CI 1.011-1.240, P = 0.030) and shorter activated partial thromboplastin time (OR: 0.967, 95% CI 0.949-0.985, P < 0.001) were associated only with preterm birth. In conclusion, preterm and early preterm birth risk factors in patients undergoing assisted IVF/ICSI are in general similar to those in natural pregnancy. The lack of some associations in the early preterm group was most likely due to the lower number of early preterm birth cases. Only embryo reduction represents an IVF/ICSI specific risk factor.
Gesehen am 26.02.2024